HSK – JĘZYKOWY PASZPORT DO CHIN. O EGZAMINIE Z PERSPEKTYWY POLAKÓW - Paliszewska-Mojsiuk, Monika; Sroka-Grądziel, Anna (Neofilolog, 2019)
HSK (Hanyu Shuiping Kaoshi – 汉语水平考试) and HSKK (Hanyu Shuiping Kouyu Kaoshi – 汉语水平口语考试) are the official Chinese language proficiency examinations for foreigners developed by Hanban (Office of Chinese Language Council International) and their results are acknowledged by many employers and institutions. They, for example, facilitate admission to universities, open the way to variety of scholarships, etc. But do they genuinely reflect the actual level of students’ proficiency? To answer this question, the authors has analyzed the structure and content of HSK and HSKK as well as their theoretical basis; they also tried to relate the Chinese examinations to the CEFR (2001). On the basis of their research, the authors point to the difficulties that Polish learners encounter when taking these examinations.